Development of Circumventricular Organs in the Mirror of Zebrafish Enhancer-Trap Transgenics - García-Lecea, Marta; Gasanov, Evgeny; Jedrychowska, Justyna; Kondrychyn, Igor; Teh, Cathleen; You, May-Su; Korzh, Vladimir (Frontiers in Neuroanatomy, 2017)
The circumventricular organs (CVOs) are small structures lining the cavities of brain ventricular system. They are associated with the semitransparent regions of the blood-brain barrier (BBB). Hence it is thought that CVOs mediate biochemical signaling and cell exchange between the brain and systemic blood. Their classification is still controversial and development not fully understood largely due to an absence of tissue-specific molecular markers. In a search for molecular determinants of CVOs we studied the green fluorescent protein (GFP) expression pattern in several zebrafish enhancer trap transgenics including Gateways (ET33-E20) that has been instrumental in defining the development of choroid plexus. In Gateways the GFP is expressed in regions of the developing brain outside the choroid plexus, which remain to be characterized. The neuroanatomical and histological analysis suggested that some previously unassigned domains of GFP expression may correspond to at least six other CVOs–the organum vasculosum laminae terminalis (OVLT), subfornical organ (SFO), paraventricular organ (PVO), pineal (epiphysis), area postrema (AP) and median eminence (ME). Two other CVOs, parapineal and subcommissural organ (SCO) were detected in other enhancer-trap transgenics. Hence enhancer-trap transgenic lines could be instrumental for developmental studies of CVOs in zebrafish and understanding of the molecular mechanism of disease such a hydrocephalus in human. Their future analysis may shed light on general and specific molecular mechanisms that regulate development of CVOs.